The effect of short-term program of resisted treadmill walking on correlation between body composition parameters and estradiol, progesterone and cortisol hormone levels in osteoporotic postmenopausal women - Tayebeh Roghani; Giti Torkaman; Shafieh Movasseghe; Mehdi Hedayati; Babak Goosheh (Vesnu Publications, 2013)
Introduction: Anabolic hormone levels reduce with increasing age that may be responsible for many forms of change in body composition. Having a regular physical activity can be considered to restore the amount of decreased hormone level. The purpose of this study was to assess the effect of resisted submaximal treadmill walking program on body composition variables and estradiol, progesterone, and cortisol hormones in osteoporotic postmenopausal women. Materials and Methods: This randomized clinical trial study was performed on twenty seven volunteer sedentary osteoporotic postmenopausal women. They were randomly divided into three groups based on walking type on treadmill: simple walking (n = 8), weighted vest (n = 9), and control (n = 10). Training sessions consisted of 6 weeks submaximal walking program with 50-60% heart rate reserve about 30 minutes daily, three times a week. In weighted vest group, subjects wore a weight vest (4-8% of body weight). Body composition parameters (Body Mass Index or BMI, fat mass, and lean mass) and levels of estradiol, progesterone and, cortisol were measured before and after 6 weeks of training. All subjects in control group did not receive any intervention. Data were analyzed using SPSS (version 17). Results: Fat was decreased and lean body mass was increased significantly in weighted vest group (P = 0.027 and P = 0.005 respectively). Correlation between fat mass and lean body mass was significant in training groups (P = 0.010 and 0.05 respectively). Although after 6 weeks levels of estradiol and progesterone hormone did not have any significant change. Cortisol hormone did prominently change in simple walking and weighted vest groups (P = 0.049 and P = 0.032 respectively) but there is no significant correlation among hormones (P > 0.050). Conclusion: It can be concluded that both training groups showed a significant correlation between body composition parameters, but external added load resulted in more improvement in these selected parameters. Although the cortisol hormone level decreased significantly in both training groups, but this decrease was more prominent in simple walking group than control. Also, there was no positive relation between anabolic hormone levels and external added load. Keywords: Resisted walking, Postmenopausal women, Body composition, Estradiol, Progesterone, Cortisol